Facility management basic philosophy and concept - Tan, Boon Chew (2006)
In new decade of 21st century, the Facility Management is view as an emerging discipline. Its roots lay in the custodial role of a building superintendent or infrastructures caretaker largely concerned with operational issues not only the maintenance cost, but more important are into productivity, efficiency and customers satisfactions. The growth of Malaysia, especially in the process toward the “Vision2020” has led to more need to introduce both tactical and strategic management function into the ultimate pursuit of making the people, society to be more productive and effective in the globalization challenges. This project (Facility Management Basic Philosophy and Concept) studying about the difference practiced and management concept and philosophy in Facilities from the difference natural of works. The operating in the Kuala Lumpur International Airport (KLIA) been chosen as the facility model or case study model in this project. This is because an airport operation is a complex and dynamic business which involved not only local community, but also had to operate as tools for macro economic externalities. Hence, it is important to understand the philosophy and concept of the airport management in order to get the healthy climate of customer satisfactions, competition, productivity and efficiency which are demanding characteristic in the new millennium of globalization challenges. From the study through the survey, it is found that the Facility Management basic philosophy and concept of the airport are managing the time, the comfort of the service and environment, and also the ease for the information. With the outcome from this project, it is hope that it will contribute for the betterment of Facilities Management industry in Malaysia.